Evaluation of wastewater surveillance for SARS-CoV-2 in a prison population: a mixed-methods approach - Jones, Gethin; Nelson, Andrew; Chadwick, David R.; Cobley, Steve; Jones, Davey L.; Perrett, Stephanie; Perry, William Bernard; Weightman, Andrew J.; Williams, Rachel C.; Thomas, Daniel Rhys (Frontiers in Public Health, 2024)
Background: Prisons are high-risk settings for the transmission of communicable disease. Robust surveillance systems are required to identify and control outbreaks. Wastewater surveillance for SARS-CoV-2 was introduced in four prisons in Wales in March 2022. We investigated its contribution to the COVID-19 surveillance programme. Methods: We evaluated prison wastewater surveillance against eight system attributes using a mixed-methods approach. Semi-structured interviews were completed with key stakeholders to assess usefulness, flexibility and acceptability. Quantitative analyses were completed to assess data quality, sensitivity, positive-predictive value, representativeness and timeliness. To assess sensitivity of the system to detect changes in incidence we carried out a time-series analysis comparing levels of virus in wastewater with trends in confirmed COVID-19 cases from clinical surveillance. Results: Interviews with stakeholders indicated that wastewater surveillance is a useful adjunct to existing case-based surveillance. However, it had limited influence on action taken within the prison, often lagging behind existing surveillance and not specific enough to target interventions. The novelty of wastewater surveillance meant stakeholders lacked confidence in interpreting the data. Despite these limitations, wastewater surveillance detected changes in SARS-CoV-2 activity in Welsh prison populations which corroborated trends in case surveillance. Conclusion: Prison wastewater surveillance, implemented in Wales for a period during the COVID-19 pandemic, was useful and should be considered as part of a wider surveillance programme in response to future SARS-CoV-2 waves, or in response to future pandemics. It is particularly beneficial in the absence of comprehensive clinical testing. We identified several limitations to address should this surveillance be re-started.